Gauging The Dependence Of Financial Performance On Assets Structure In The Nigerian Banking Industry - Chizoba, Alozieuwa Nneka; Priscilla, Egbo Obiamaka; Ume, Kalu Ebere; Ukpere, Wilfred (Migration Letters, 2024)
This paper examines the interaction of asset structure and financial performance in the largest banking system in Africa – Nigeria, using data from 1996 to 2022. Five leading banks in the system with national, regional and international spread were used for the study. Results from the panel estimation reveal that asset structure has a positive and significant impact the financial performance of the studied banks. Earning assets like loans and advances were found to be the major contributors to financial performance over other operational assets like non-current assets. We argue that managers and regulators of banks should give attention to the asset mix of banks for the imperatives of enhancing earnings, liquidity and stability of the banks as well as the system at large.